Sous vide technology for convenience seafood products - Doncillo, Leonora D. (Iloilo University of the Philippines in the Visayas, 2005)
The study was conducted to detect the presence of anaerobes and Listeria monocytogenes in minimally processed convenience seafood products in the market and to evaluate the effects of sous vide technology to the microbiological, physico-chemical and sensorial quality attributes of the selected seafood product. Results revealed that out of 10 collected samples, three (3 samples having the same brand were found to be positive for anaerobes. A sample of this brand was subjected to Lsteria monocytogenes analysis during Reveal screening test kit. Three out of the twenty lots tested were found to be positive for Listeria monocytogenes. This lot was then subjected to sous vide processing using different time and temperature combinations. Result showed that a combination of 50 C for 5 mins (Pv o.997) for sous vide processing was effective to eliminate Listeria monocytogenes in fish ball samples. Further, it was noted that anaerobes present in the sample were all eliminated at temperature of 80 C for 10 min (Pv 1.083). Moreover, there is no significant difference (P>0.01) in both physico-chemical composition such as moisture, crude protein, pH, and Aw as well as sensorial quality attributes specifically, the texture, color and odor between sous vide and non-sous vide vacuum packed fish ball samples. This indicates that sous vide processing did not alter the physico-chemical composition of fish ball samples and it has improved its quality attributes while maintaining the samples free from Listeria monocytogenes.
Thesis (M.S. Fisheries-Fish Processing Technology.) -- Miagao, Iloilo : U.P. in the Visayas, April 2005.
Keywords: Seafoods; Sous vide